Protective potential of Lactobacillus species in lead toxicity model in broiler chickens. (2nd November 2016) - Jahromi, M. F.; Liang, J. B.; Ebrahimi, R.; Soleimani, A. F.; Rezaeizadeh, A.; Abdullah, N.; Shokryazdan, P.
Abstract : To alleviate adverse effects of heavy metal toxicity, diverse range of removing methods have been suggested, that is usage of algae, agricultural by-products and microorganisms. Here, we investigated lead (Pb) biosorption efficacy by two lactic acid bacteria species (LABs) in broiler chickens. In an in vitro study, Pb was added to culture medium of LABs ( Lactobacillus pentosus ITA23 and Lactobacillus acidipiscis ITA44) in the form of lead acetate. Results showed that these LABs were able to absorb more than 90% of Pb from the culture medium. In follow-up in vivo study, LABs mixture was added to diet of broiler chickens contained lead acetate (200 mg/kg). Pb exposure significantly increased lipid peroxidation and decreased antioxidant activity in liver. The changes were recovered back to normal level upon LABs supplementation. Moreover, addition of LABs eliminated the liver tissue lesion and the suppressed performance in Pb-exposed chicks. Analysis of liver and serum samples indicated 48% and 28% reduction in Pb accumulation, respectively. In conclusion, results of this study showed that L. pentosus ITA23 and L. acidipiscis ITA44 effectively biosorb and expel dietary Pb from gastrointestinal tract of chickens.